Diffusion d’un savoir et légitimation d’une pratique thérapeutique dans les revues médicales : l’exemple de la transplantation d’organes en Suisse entre 1950 et 1990 - Alexia Cochand (Amnis)
The purpose of this article is to describe how organ transplantation was presented in two Swiss medical journals between 1950 and 1990. Firstly, the transmission of information will be considered during period (1950-1970) when the transplantation was not developed in Swiss hospitals. The means employed to present this medical practice without proven expertise at local level will be identified. Secondly, we will focus on the transmission of information between 1970 and 1990 and on the role of the actors involved in the emergence of organ transplantation.